Cochlear Implant Electrode Impedance as Potential Biomarker for Residual Hearing - Wimmer, Wilhelm; Sclabas, Luca; Caversaccio, Marco; Weder, Stefan (Frontiers in Neurology, 2022)
Introduction & Objectives: Among cochlear implant candidates, an increasing number of patients are presenting with residual acoustic hearing. To monitor the postoperative course of structural and functional preservation of the cochlea, a reliable objective biomarker would be desirable. Recently, impedance telemetry has gained increasing attention in this field. The aim of this study was to investigate the postoperative course of residual acoustic hearing and clinical impedance in patients with long electrode arrays, and to explore the applicability of impedance telemetry for monitoring residual hearing. Methods: We retrospectively analyzed records of 42 cochlear implant recipients with residual hearing covering a median postoperative follow-up of 25 months with repeated simultaneous pure tone audiometry and impedance telemetry. We used a linear mixed-effects model to estimate the relation between clinical electrode impedance and residual hearing. Besides the clinical impedance, the follow-up time, side of implantation, gender, and age at implantation were included as fixed effects. An interaction term between impedance and follow-up time, as well as subject-level random intercepts and slopes, were included. Results: Loss of residual hearing occurred either during surgery or within the first 6 postoperative months. Electrode contacts inserted further apically (i.e., deeper) had higher impedances, independent of residual hearing. The highest impedances were measured 1 month postoperatively and gradually decreased over time. Basal electrodes were more likely to maintain higher impedance. Follow-up time was significantly associated with residual hearing. Regardless of time, we found that a 1 kOhm increase in clinical impedance was associated with a 4.4 dB deterioration of residual hearing (p<.001). Conclusions: Pure tone audiometry is the current gold standard for monitoring postoperative residual hearing. However, the association of clinical impedances with residual hearing thresholds found in our study could potentially be exploited for objective monitoring using impedance telemetry. Further analysis including near-field related impedance components could be performed for improved specificity to local immune responses.